Emerging Anthelmintic Resistance in Poultry: Can Ethnopharmacological Approaches Offer a Solution? - Zirintunda, Gerald; Biryomumaisho, Savino; Kasozi, Keneth Iceland; Batiha, Gaber El-Saber; Kateregga, John; Vudriko, Patrick; Nalule, Sarah; Olila, Deogracious; Kajoba, Mariam; Matama, Kevin; Kwizera, Mercy Rukundo; Ghoneim, Mohammed M.; et al. (Frontiers in Pharmacology, 2022)
Limited pharmacological studies have been conducted on ethnomedical plant species used against poultry helminths. The objective of this study was to provide a basis for ethnomedicinal anthelmintics as possible alternatives against poultry anthelminthic resistance. The study justified the need for alternative anthelmintics. The study places emphasis on the increasing anthelmintic resistance, mechanism of resistance, and preparational protocols for ethnomedicinal anthelmintics and their associated mechanism of action. Pharmaceutical studies on ethnomedical plants as alternative therapies for the control of coccidian parasites have not been fully explored especially in several developing countries. Ethnomedicinal plants from a broad range of species produce a wide variety of compounds that are potential ethnomedicinal anthelmintics candidates. Important phenolic acids have been found in Brassica rapa L. and Terminalia avicenniodes Guill. &Perri that affect the cell signaling pathways and gene expression. Benzo (c) phenanthridine and isoquinoline alkaloids are neurotoxic to helminths. Steroidal saponins (polyphyllin D and dioscin) interact with helminthic mitochondrial activity, alter cell membrane permeability, vacuolation and membrane damage. Benzyl isothiocyanate glucosinolates from interfering with DNA replication and protein expression, while isoflavones from Acacia oxyphylla cause helminth flaccid paralysis, inhibit energy generation, and affect calcium utilization. Condensed tannins have been shown to cause death of nematodes and paralysis leading to expulsion from the gastrointestinal tract. Flavonoids from Chenopodium album L and Mangifera indica L act through action of phosphodiesterase and Ca2+-ATPase, and flavonoids and tannins have been shown to act synergistically and are complementary to praziquantel. Artemisinins from Artemisia cina O. Berg are known to disrupt mitochondrial ATP production. Terpenoids from Cucurbita moschata L disrupt neurotransmission leading to paralysis as well as disruption of egg hatching. Yeast particle encapsulated terpenes have been found to be effective for the control of albendazole-resistant helminths.